Anecdotes of the late Samuel Johnson, LL.D. : During the Last Twenty Years of His Life - Piozzi, Hester Lynch, 1741-1821; Morley, Henry, 1822-1894 (Salt Lake City, UT : Project Gutenberg, 2000)
"Anecdotes of the late Samuel Johnson, LL.D." by Hester Lynch Piozzi is a biographical work published in 1786. Drawing from her personal notes and twenty years of friendship with the renowned literary figure, Piozzi presents intimate glimpses into Samuel Johnson's manners, genius, and everyday life. Written in Italy after Johnson's death, the book sold out immediately, reportedly keeping King George III reading through the night. Despite mixed critical reception$1 (Bsome calling it "rubbish," others praising its liveliness$1 (Bthe work established Piozzi's reputation as an eighteenth-century writer. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Anecdotes_of_the_Late_Samuel_Johnson
Release date is 2000-12-01
This eText was transcribed from the 1901 Cassell and Company edition by Les Bowler
Keywords: Johnson, Samuel, 1709-1784